Rationalization of Public Road Passenger Transport by Merging Bus Lines on the Example of Zadar County - Kos, Goran; Brlek, Predrag; Franolić, Igor (Promet - Traffic&Transportation, 2012)
This study consists of the analysis of public passenger transport in Zadar County, that is, transport on the County and school lines and suggestions of transport rationalization. The rationalization comprises the application of the County and school lines integration, as well as suggestions of other measures which aim to reduce transport costs financed by Zadar County. The objectives to rationalize public passenger transport have been defined, all County transport lines of schoolchildren and other passengers have been analysed as well as actual deficiencies in the city, County and school transport needs. Road transport infrastructure, carriers and transportation vehicles have been analysed. The future transport demand has been reviewed and the prediction of passengers on lines has been provided. Within the next five to ten years no relevant changes will take place, meaning that the balance in transport supply and demand will not be disrupted significantly. This study presents the measures for transport cost reduction and increase in the safety level in the performance of public transport.